ONLINE REVIEWS, RATINGS, AND PURCHASE INTENTION IN SOCIAL COMMERCE: THE MEDIATING ROLE OF PRODUCT PHOTOS ON TIKTOK LIVE STREAMING - Melisa Amelia Yesmi; Lina Saptaria (SOSIOEDUKASI, 2025)
This study aims to analyze the influence of Online Customer Rating (OCRt), Online Customer Reviews (OCR), and product photos on consumer purchasing interest in Camille Beauty products on TikTok Shop by referring to the Stimulus–Organism–Response (S-O-R) theoretical framework. The research approach uses a survey-based quantitative method, with a sample of 128 respondents from Generation Z who are TikTok Shop Live Streaming users and have experience viewing or purchasing Camille Beauty products. Data analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach through SmartPLS 4.0 software. The results show that OCRt, OCR, and product photos contribute significantly in shaping customer purchasing interest. In addition, product photos are proven to be able to mediate the relationship between OCRt and purchasing interest, as well as between OCR and customer purchasing interest on TikTok Shop, thereby strengthening the relationship between customer experience-based information and purchasing decisions. This study adds to the literature on digital consumer behavior, particularly in the context of live streaming-based social commerce, by confirming that visual elements, such as product photos, play a significant mediating role in linking OCRt and OCR to purchase intention. The results provide recommendations for businesses and the skincare brand Camille Beauty to optimize their digital marketing strategies on TikTok Shop Live Streaming.